Strategi Internal Dan Eksternal Umkm Sambal Pecel Madiun Dalam Meningkatkan Daya Saing Usaha - Trimintarsih, Titin (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
Madiun sambal pacel business is indeed a characteristic that is inherent, has many consumers. However, business actors also face a high level of competition. Therefore, internal and external strategies are needed to increase business competitiveness. The method in this study uses SWOT analysis of the IFAS and EFAS methods with the distribution of 25 questionnaires. The results of the SWOT Analysis show that internal factors have a score of 8.07 and external factors have a score of 9.29. From the results of internal and external factors, a series of scores are produced: Strengths (Strengths / S) = 5.05, Weaknesses (Weaknesses / W) = 3.02, Opportunities (Opportunities / O) = 4.69 and Threats (Threats / T) = 4.60. Located in the Growth quadrant.